SOCIAL RELIANCE AND MASTERY OF ECONOMIC LOCATION AT SAGAN INTERSECTION COMMUNITY IN YOGYAKARTA - Ahmad Subhan (Pusbindiklat - LIPI, 2011)
This research is an empirical study on poverty in the basic level, the poor themselves. This exploratory research revealed a profile and picture of poverty in urban area, namely Sagan’s intersection community in Yogyakarta with natural inquiry approach, which is trying to obtain information about people by observing and interviewing them in their natural environment. Results showed that this community is not entirely including as the poor, as seen in plain view. This community a mastery of economic location based on seniority. The first person who occupies the location has greater rights than other members. The study also found the phenomenon of socialreliance of the poor. This phenomenon appears as the effects of social values that exist in urban communities. Charity, aid, and other charities serve as wealthy people’s self obligations. Social capital which could encourage the autonomy of the community precisely can bring people into the culture of poverty.